Land, Violent Conflict and Development - Pons-Vignon, Nicolas (OECD Development Centre Working Papers, 2004)
Land dynamics are context specific and rapidly changing, and conflicts related to them do not systematically escalate into violence. One way of framing the discussion is to consider change in the structures of power governing the management of resources in rural areas as necessary to achieve greater efficiency and equity. Since such change will be opposed by beneficiaries of the system in place, the transformation of agriculture is bound to be marred by conflicts of various intensity levels. At the heart of these conflicts lies land because of its very high material and symbolic values. Evidence shows that (a) whether they result from pre-existing agrarian tensions or not, conflict situations in rural societies deeply affect the politics of land, and (b) whether it is at the heart of a conflict or gets dragged into it, land requires a careful approach by policy makers because it is a central element in the evolution of societies. As a result, policies pertaining to land can ...